Welcome to our community

Be a part of something great, join today!

KE Deduction

lyd123

New member
Dec 22, 2018
12
Hi, the question and Ke logic rules are attached.

This is my attempt at the question.

$1. P \land (R\implies Q) $ Premise
$2. ( P \land Q ) \implies \lnot S) $ Premise
$3. ( P \land S) \implies R) $ Premise
$4. \lnot S $ Conclusion
$5. P \land Q$ $ \beta 2,4$
$6. P $ $ \alpha 5$
$7. Q$ $ \alpha 5$
$8. R\implies Q $ $ \alpha 1$

I don't think the lines I wrote after this make a lot of sense. Usually a contradiction would be found, but in this case I dont seem to find a contradiction. I think maybe I have to negate the conclusion, I thought it was already negated because of the \lnot. But how do I know when the argument form is valid (invalid being if there is a contradiction).


Thank you for any help. :)

2019-01-03.png
2019-01-03 (1).png
 

Evgeny.Makarov

Well-known member
MHB Math Scholar
Jan 30, 2012
2,488
I assume that $\neg S$ is the original conclusion, not its negation.

You cannot derive $P\land Q$ from $P\land Q\implies \neg S$ and $\neg S$.

To prove $\neg S$, one must use the law of excluded middle, or the branching rule. From premise 1 we have $P$ and $R\implies Q$. If $S$, then we get $R$ from premise 3, $Q$ from premise 1 and finally $\neg S$ from premise 2. If $\neg S$, then nothing is left to do.
 

lyd123

New member
Dec 22, 2018
12
Thank you, I understand now.If an argument was valid, how would we know? For example, in this case if the the original was S and the negated conclusion is ¬S ?

1.P∧(R⟹Q) Premise
2.(P∧Q)⟹¬S Premise
3.(P∧S)⟹R Premise
4.¬S Negated Conclusion
 

Evgeny.Makarov

Well-known member
MHB Math Scholar
Jan 30, 2012
2,488
These premises do not imply $S$. The easiest way to see this is to find a counterexample, i.e., an assignment of truth values to variables that makes all premises true and the conclusion false. In this case it is $R=Q=S=F$ and $P=T$.